A Hollow Tube‐on‐Tube Architecture of Carbon‐Tube‐Supported Nickel Cobalt Sulfide Nanotubes for Advanced Supercapacitors. Issue 4 (23rd March 2017) - Wang, Nannan; Wang, Yanjie; Cui, Shizhong; Hou, Hongwei; Mi, Liwei; Chen, Weihua
Abstract: The nanotube structure has unique advantages, such as a large electroactive surface area and shorter diffusion pathway for ions/electrons for energy storage. In this paper, we fabricated a novel supercapacitor electrode material based on a composite material with a hollow tube‐on‐tube architecture. This architecture, which was derived from the sustainable Juncus roemerianus, consisted of nickel cobalt sulfide nanotubes coating the exterior and interior of carbon tubes. The obtained hollow tube‐on‐tube structure is similar to a reservoir, in which ions/electrons can diffuse via a bi‐directional method and supply and transfer to the carbon tube interface. Consequently, this structure can probably provide more electrochemically active sites for its application in high‐performance asymmetric supercapacitors (ASCs). The assembled ASC device also presents superior specific capacitance (83 F g −1 at the current density of 0.5 A g −1 ), high energy density (27.7 Wh kg −1 at a power density of 263.6 W kg −1 ), and good cycling stability (72.23 % capacitance retention after 3000 cycles). Therefore, the NiCo2 S4 /bio‐carbon electrode with hollow tube‐on‐tube structure is not only a promising electrode material, but also can be applicable to energy storage and conversion devices. Abstract : Totally tubular : A two‐electrode system was assembled by using a hollow tube‐on‐tube carbon tube/NiCo2 S4 nanotube (CT/NCS‐tube) sample as a positive electrode and activated carbon (AC) as a negative electrode. Electrochemical characterization was performed to evaluate the electrode.